Analysis of the Implementation of Training and Development Programs for Teachers in the Context of Curriculum Change: Evaluation and Recommendations - Muhammad Ybnu T; Eli Retnowati; Maftuhah Dewi; Klemens Mere; Bayu Purbha Sakti (Dinasti Publisher, 2024)
The implementation of training and development programs for teachers plays a crucial role in enhancing their skills and capabilities, especially in the context of curriculum change. This study conducts a comprehensive analysis of such programs, focusing on their effectiveness, challenges, and areas for improvement. Through a literature review approach, various scholarly works, empirical studies, and best practices are examined to evaluate the impact of training and development initiatives on teacher performance and student outcomes. The evaluation encompasses aspects such as program design, delivery methods, content relevance, participant engagement, and organizational support. It delves into the strategies employed to address the evolving needs of teachers amid curriculum transformations, considering factors like technological integration, pedagogical innovations, and curriculum alignment. Furthermore, the study explores the role of continuous professional development in sustaining teacher motivation, fostering a culture of lifelong learning, and adapting to dynamic educational landscapes. Based on the analysis, several recommendations are proposed to enhance the efficacy of training and development programs for teachers. These recommendations encompass tailored professional development pathways, collaborative learning communities, mentorship programs, feedback mechanisms, and resource allocation strategies. The findings of this study contribute valuable insights to educational policymakers, administrators, and stakeholders involved in designing and implementing teacher training initiatives within the framework of curriculum change.